From Anxious Spaces to Harmonious Relations? Interracial Marketplace Interactions Through the Lens of Consumer Psychology - Grier, Sonya A.; Johnson, Guillaume D.; Scott, Maura L. (Journal of Consumer Psychology, 2022)
Interracial interactions abound in the marketplace and are at the core of many consumer experiences across commercial, health, and social settings. The creation of harmonious interracial interactions is a focal target of private, nonprofit, and governmental efforts to transform consumer markets worldwide. Yet both research and practice highlight the challenge of achieving such interactions. Despite their centrality to consumer experience and social significance, interracial interactions have received limited attention in the consumer psychology literature. Understanding the particular role of interracial interactions in how consumers choose, buy, and consume products, services, and experiences is essential to address racial inequity in the marketplace. In this research, we identify extant interdisciplinary research to conceptualize the consumer psychology underlying interracial marketplace interactions. We analyze this literature to summarize the state of the knowledge, identify important research gaps, and develop an organizing framework for prior and future research. Our analysis highlights priorities for future research supportive of harmonious interracial interactions that promote consumer equity and contribute to societal well‐being.